Islamic Political Movements in Indonesia: From Nahdlatul Ulama to Islamist Parties in the Post-Reformasi Era - Mursyidin Mursyidin; Chai Pao; Napat Chai (Yayasan Adra Karima Hubbi, 2025)
The post-Reformasi era in Indonesia since 1998 has witnessed a dynamic resurgence of Islamic politics, featuring a complex landscape of both large moderate civil society organizations and formal Islamist political parties. This study aimed to comparatively analyze the evolution, political strategies, and societal impact of these diverse Islamic movements in Indonesia’s democratic transition. A qualitative research methodology was employed, utilizing a case study approach. Data was gathered through discourse analysis of party manifestos and public statements, as well as in-depth interviews with political and religious leaders. The findings reveal a strategic divergence: Nahdlatul Ulama has largely focused on influencing politics from a civil society perspective, promoting cultural Islam and pluralism. In contrast, Islamist parties have pursued formal state power, often employing identity politics. This has created a continuous negotiation within the public sphere between substantive Islamic values and formalist political agendas. The study concludes that Indonesian Islamic political movements are not monolithic. The enduring influence of moderate mass organizations acts as a crucial counterbalance to the formal political aspirations of Islamist parties, shaping a unique and contested model of Islamic democracy.